Hyperuricemia is Associated With 2- and 5-Year Adverse Outcomes in Patients With ST-Segment Elevation Myocardial Infarction Undergoing Percutaneous Coronary Intervention - Xiao-Fang Tang (Frontiers in Endocrinology, 2022)
BackgroundHyperuricemia has recently been identified as a risk factor of cardiovascular diseases; however, prognostic value of hyperuricemia in patients with ST-segment elevation myocardial infarction (STEMI) remained unclear. Simultaneously, the mechanism of this possible relationship has not been clarified. At present, some views believe that hyperuricemia may be related to the inflammatory response. Our study aimed to investigate the association between hyperuricemia and long-term poor prognosis and inflammation in STEMI patients undergoing percutaneous coronary intervention (PCI).MethodsA total of 1,448 consecutive patients with STEMI were studied throughout 2013 at a single center. The primary endpoint was all-cause death at 2- and 5-year follow-up. Inflammatory biomarkers were collected on admission of those patients: high sensitive C-reactive protein (hs-CRP), erythrocyte sedimentation rate (ESR), and white blood cell (WBC) count.ResultsHyperuricemia was associated with higher 2- and 5-year all-cause death in STEME patients compared to normouricemia (5.5% vs. 1.4%, P <0.001; 8.0% vs 3.9%, P = 0.004; respectively). After multivariable adjustment, hyperuricemia was still an independent predictor of 2-year all-cause death (hazard ratio (HR) =4.332, 95% confidence interval (CI): 1.990–9.430, P <0.001) and 5-year all-cause death (HR =2.063, 95% CI: 1.186–3.590, P =0.010). However, there was no difference in hs-CRP, ESR, and WBC count on admission in STEMI patients with hyperuricemia compared to normouricemia (P >0.05).ConclusionsHyperuricemia was associated with higher risks of 2- and 5-year all-cause deaths in patients with STEMI undergoing PCI. However, this study did not find a correlation between hyperuricemia and inflammatory responses in newly admitted STEMI patients.